Against the World: Anti-Globalism and Mass Politics between the World Wars - O'Rourke, Kevin Hjortshøj (Journal of Economic Literature, 2024)
Kevin Hjortshoj O'Rourke of NYU Abu Dhabi reviews “Against the World: Anti-Globalism and Mass Politics between the World Wars” by Tara Zahra. The Econlit abstract of this book begins: “Explores the development of nationalism in the twentieth century after World War I, discussing significant events that contributed to the rise of anti-globalization policies and social movements.”